Structural Adjustment Programs in Turkey in terms of Income Distribution (1980-2000) - DOGAN, Alper (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2016)
The major obstacle for the instable and developing economies of the developing countries were seen as governmentintervention in the economy. This led to debt crisis for emergency economies in the beginning of 1980s in which theamount of loans they borrowed with low interest rates increased very fast after rising interest rates. This problem gavenew objectives to the IMF and the World Bank to stabilize those economies under deficit pressures with a more profoundand comprehensive package of policy reforms which is known by its famed name, Structural Adjustment Programs. Thephilosophy was the minimalization of the state via trade and financial liberalizations. However, the last situation indicates that there is a certain income gap among different states and this seems like a big dilemma concerning the globalizedworld after SAPs. And this study tried to explain one of the transition periods of the globalization in Turkey under the WorldBank-IMF co-operated structural adjustment program in the early 1980s and the effect of the program on incomedistribution in Turkey until 2001 crisis.